PENINGKATAN MINAT MEMBACA MELALUI PERMAINAN POP-UP CARD ANAK KELAS B DI PAUD AULIA PALEMBANG - Yurinda Withasari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The study aims to determine whether the interest class B in PAUD Aulia Palembang can be improved through the pop-up card game. The study was conducted for 22 children aged 5 to 6 years in grade B PAUD Aulia Palembang, in January-February 2018. The method used is a model of action research Kemmis Mc Taggart. The study was conducted in 16 sessions divided into two cycles. In every cycle there are four stages of activity: planning, action, observation and reflection. Data were analyzed using analysis of quantitative and qualitative analysis. The results showed that interest in reading class B in PAUD Aulia Palembang can be improved through the pop-up card game. The reading interest class B in PAUD Aulia Palembang are on a score of 50 on the pre-intervention phase. reading interest class B in PAUD Aulia Palembang increased to 77.3 at the end of cycle I, and continued to increase to 104 by the end of cycle II. The results of the study implies that the pop-up card game could be one way to improve the reading interest